Increase of oxygen permeability on metal/oxide interface during high temperature oxidation of Fe-Cr alloys in water vapor at 1073 K - Ani, Mohd Hanafi; Setiawan, Asep Ridwan; Hens, Saputra; Othman, Raihan; Ueda, Mitsutoshi; Kawamura, Kenichi; Maruyama, Toshio (2010)
Many studies1-3 have shown that oxidation rates in humid environment are higher than in dry environment. The formation of Cr2O3 scale during high temperature oxidation is beneficial in protecting metals from severe oxidizing environment. A dilute solid solution, such as Fe-Cr alloy with small Cr concentrations, forms internal oxide of Cr2O3 when exposed at high temperature. Further addition of Cr in the alloy leads to the development of protective Cr2O3 scale. The oxidation of Fe-Cr alloys was conducted in a closed apparatus at 1073 K and the oxygen partial pressure of 1.1 x 10-14 Pa, which was fixed by a Fe/FeO buffer. To prepare the humid condition, Ar-5% H2 gas mixture of 3 x 104 Pa was filled in the apparatus, which provided the water vapor pressure of 3.3 x 102 Pa. The objective of this study is to evaluate the effects of water vapor to the oxygen permeability in α-Fe at 1073 K.